Effectiveness of Focused Obstetric Ultrasound Training to Nurses from Remote Health Posts to Improve Pregnancy Outcome and Reduce Morbidity - Joshi, Jagadish; Sherpa, Mingmar Gyelzen; Sherpa, Lhamo Yangchen; Lama, Neema; Maharjan, Manju; Lama, Igroom Dolma; Khadka, Smita (Journal of Nepal Health Research Council, 2023)
Background: A rural ultrasound program was started in Nepal in order to detect complicated pregnancies early in health post where radiologists are not available to provide their services. The study aims to investigate whether focused obstetric ultrasound trained nurses were capable of detecting high risk pregnancy at an early stage in their health post and refer them to higher centre timely so that they are taken care properly.Methods: The study site for research were health posts and hospitals where the rural ultrasound program had been conducted in districts of Sudurpashchim province. The referral centres within Sudurpashchim province were assessed for cross verification of diagnosis and pregnancy outcome of referred cases. Quantitative data was collected from health posts and hospitals ultrasound log book where women who had accessed obstetric ultrasound services during pregnancy. Qualitative data was collected from nurses who have completed training. The data was verified from log-book registered in the health post and hospitals. All the quantitative data was entered and analysed. Results: Cross verified data revealed that focused obstetric ultrasound received nurses identified cases been verified same diagnosis in referral hospitals with 66 cases. In-depth interview with 28 nurses revealed that training received by them was effective in minimizing preventable maternal and neonatal mortality and morbidity.Conclusions: Focused obstetric ultrasound in rural and under-resources communities like in Nepal has the potential to improve access and quality of health care services and can result in an increased uptake of antenatal care service utilisation. Keywords: Complicated pregnancies; health post; nurses; obstetric ultrasound